Sebaran Populasi dan Klasifikasi Resistensi Eleusine indica terhadap Glifosat pada Perkebunan Kelapa Sawit di Kabupaten Deli Serdang - Koko Tampubolon; Edison Purba; Diana Sofia Hanafiah; Mohammad Basyuni (Universitas Sebelas Maret, 2018)
Eleusine indica populations on oil palm plantations in Deli Serdang Regency have not been reported to be resistant to glyphosate. This study was aimed to report distribution and resistance classification of E. indica population on oil palm plantations in Deli Serdang Regency. The research was conducted on Weed Research Center in Faculty of Agriculture, Universitas Sumatera Utara from October 2016 until August 2017. This research used Randomized Block Design with recommended dose at 720 g a.i.ha-1 of glyphosate and three replications. Population ESU0 (from Politeknik Negeri Medan Ball Field) as a comparison. Data on average survival, mortality, dry weight, resistance classification of E. indica were analyzeds using IBM SPSS Statistics 20 software. The results showed that there were 12 E. indica populations classified as glyphosate-resistant (56.52%), 7 glyphosate-resistant developing (30.43%), and 4 populations classified as glyphosate-susceptible (13.04%) with the recommended dose at 720 g a.i.ha-1 from oil palm plantations in Deli Serdang Regency.